Antimicrobial activity of a quaternized BODIPY against Staphylococcus strains - Tekdas, Duygu Aydin; Viswanathan, Geetha; Topal, Sevinc Zehra; Looi, Chung Yeng; Wong, Won Fen; Tan, Grace Min Yi; Zorlu, Yunus (Royal Soc Chemistry, 2016)
A novel BODIPY derivative was designed for biomedical applications. Its mono-quaternized structure ensured its water-solubility and suitable amphiphilicity. Showing no singlet oxygen generation to avoid damage to healthy cells, this new derivative proved to be an extremely promising antimicrobial agent, with activity equal or superior to ampicillin against MRS Staphylococcus strains with no short-term resistance issue. Its activity against MSS Staphylococcus strains was largely superior to those of ampicillin and reached the activity of vancomycin against MSS S. epidermidis. This latter result is in particular extremely promising for the treatment of hospital-acquired infections. Also the fluorescence properties of BODIPY allowed imaging of the uptake.
Keywords: Aureus; Discovery; Probes; Dyes